Developmental Epidemiological Courses Leading to Antisocial Personality Disorder and Violent and Criminal Behavior: Effects by Young Adulthood of a Universal Preventive Intervention in First- and Second-Grade Classrooms - Petras, Hanno (2008)
BACKGROUND: Antisocial personality disorder (ASPD), violent and criminal behavior, and drug abuse disorders share the common antecedent of early aggressive, disruptive behavior. In the 1985–1986 school year teachers implemented the Good Behavior Game (GBG), a classroom behavior management strategy targeting aggressive, disruptive behavior and socializing children to the student role. From first grade through middle school the developmental trajectories of 2,311 students from 19 Baltimore City Public Schools were examined. This article reports the GBG impact on these trajectories and ASPD and violent and criminal behavior by age 19–21 among the selected 768 students. METHODS: In five urban poor to lower-middle class predominately African American areas, three to four schools were matched and within each set randomly assigned to one of three conditions: 1) the GBG, 2) a program directed at reading achievement, or 3) the standard program. Classrooms and teachers were randomly assigned to intervention or control. Measures at 19–21 included self reports and juvenile court and adult incarceration records. Intervention impact was assessed via General Growth Mixture Modeling based on repeated measures of aggressive, disruptive behavior. RESULTS: Three trajectories of aggressive, disruptive behavior were identified. By young adulthood, there was significant reduction in rates of ASPD and violent and criminal behavior among GBG males in the high aggressive, disruptive trajectory. REPLICATION: A replication was implemented with the next cohort of first-grade children using the same teachers during the following school year, but with diminished mentoring and monitoring of teachers. The results showed generally non-significant effects in the same direction.